ATP/ADP binding to a novel nucleotide binding domain of the reticulocyte-binding protein Py235 of Plasmodium yoelii - Ramalingam, Jeya Kumar (2011)
The mechanism by which a malaria merozoite recognizes a suitable host cell is mediated by a cascade of receptor-ligand interactions. In addition to the availability of the appropriate receptors, intracellular ATP plays an important role in determining whether erythrocytes are suitable for merozoite invasion. Recent work has shown that ATP secreted from erythrocytes signals a number of cellular processes. To determine whether ATP signaling might be involved in merozoite invasion, we investigated whether known plasmodium invasion proteins contain nucleotide binding motifs. Domain mapping identified a putative nucleotide binding region within all members of the reticulocyte-binding protein homologue (RBL) family analyzed. A representative domain, termed here nucleotide binding domain 94 (NBD94), was expressed and demonstrated to specifically bind to ATP. Nucleotide affinities of NBD94 were determined by fluorescence correlation spectroscopy, where an increase in the binding of ATP is observed compared with ADP analogues. ATP binding was reduced by the known F1F0-ATP synthase inhibitor 7-chloro-4-nitrobenzo-2-oxa-1,3-diazole. Fluorescence quenching and circular dichroism spectroscopy of NBD94 after binding of different nucleotides provide evidence for structural changes in this protein. Our data suggest that different structural changes induced by ATP/ADP binding to RBL could play an important role during the invasion process.